The National SOM Survey 1994 - SOM Institute, University of Gothenburg (University of Gothenburg, 1996)
Since 1986 the research project ´Samhälle Opinion Massmedia´ (SOM) has been carrying out an annual nation-wide survey of Swedish opinions. This is accordingly the ninth survey in this series. The questionnaire was divided into six subject fields: mass media; politics and society; energy, nuclear power and environment; Sweden and the rest of the world; leisure; and background. Most of the questions are replications of questions asked in one or several previous SOM-surveys. New questions dealt with equality between men and women; Sweden´s future relation to the European Union; confidence in various groups concerning information about the European Union; the importance of various issues for the respondent´s own opinion on a Swedish membership of the European Union; opinion on establishment of various activities in the respondent´s own municipality; the rights of various ethnical groups to look after their interests; and radio channels listened to. The respondents also had to place the political parties on a scale measuring attitude towards christian values.

Purpose:

The main purpose is to establish time series that enable researchers to analyse how various changes in society affect people's attitudes and behaviour.

Detta är den nionde undersökningen i serien Riks-SOM, en nationell frågeundersökning med syfte att kartlägga den svenska allmänhetens vanor och attityder på temat samhälle, opinioner och medier.

1994 års undersökning består av sex sammanhållna delar: massmedier; politik och samhälle; energi, kärnkraft och miljö; Sverige och omvärlden; fritid samt bakgrundsfrågor. Genom att frågor ställts på ett likartat sätt över tid finns det i SOM-serien tidsserier om bland annat medieanvändning, politik, kärnkraftsopinion och förtroende för olika samhällsinstitutioner och grupper.

Nya frågeställningar i denna undersökning tar upp jämställdhet mellan kvinnor och män; Sveriges framtida förhållande till EU; förtroende för olika grupper när det gäller information i EU-frågor; olika frågors betydelse för den egna åsikten om ett svenskt EU-medlemskap; inställning till etablering av olika verksamheter i den egna kommunen; olika etniska gruppers rätt att ta tillvara sina egna intressen; samt lyssnande på olika radiokanaler. Respondenterna fick även placera de politiska partierna på en skala efter deras inställning till kristna värden.

Syfte:

Huvudsyftet är att etablera tidsserier som gör det möjligt att analysera hur olika samhällsförändringar påverkar människors attityder och beteenden.
Den nationella SOM-undersökningen 1994
Riks-SOM 1994
Keywords: elections; val; mass media; massmedia; population migration; migration; participation; deltagande; public sector; offentlig sektor; religion; religion; ethics; etik; international relations; internationella relationer; energy; energi; environment; miljö; health; hälsa; leisure time; fritid; internal politics; inrikespolitik; gender role; könsroll; minority groups; minoritetsgrupp; CORS; CORS; Media; Media; Environment and conservation; Miljö och naturvård; Energy and natural resources; Energi och naturresurser; Political behaviour and attitudes; Politiska beteenden och attityder; International politics and organisations; Internationell politik och organisationer; Leisure, tourism and sport; Fritid, turism och sport; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap; Media and Communication Studies; Medie- och kommunikationsvetenskap